'Self-Esteem' Di Kalangan Pelajar Luar Bandar - Zainurin, Hj. Ahmad (1998)
The purpose of this research is to find out the degree of self-esteem among rural students in Larut Matang and Selama District. It is being done by comparing the min grade self-esteem with the sosio-demography features. The degree of self-esteem is measured by using the macro and micro-scale. The study is done by survey method using questionnaires. This method is chosen because of it’s viability in gathering information to answer the research questions. By using Yoong Suan (1993) instrument with some alternations from the Indiana Student Scale, a pilot test was carried out with the ‘alpha-Crombach methods to find out the validity of the instrument. The result from the test showed a 0.8767 mark. Two hundred respondents have been chosen at random from ten different schools in the district. All data collected had been analyzed using the variants analysis method. The results showed significance difference towards students degree of self-esteem in relation to race, religion, living area, physical appearance, social and family relationship. Sex has no significance difference or influence towards the degree of self-esteem among the respondents. The research found that majority of the students have an average degree of self-esteem.